Frequency of missing teeth and reduction of mesiodistal tooth width in Japanese patients with tooth agenesis - Norihisa Higashihori; Jun-ichi Takada; Minami Katayanagi; Yuki Takahashi; Keiji Moriyama (Progress in Orthodontics, 2018)
Abstract Background Tooth agenesis can involve one or more congenitally missing teeth (CMT) and is the most common congenital dental anomalies in humans. Tooth agenesis and reduction of mesiodistal tooth width are reportedly associated, suggesting that the pathogenesis of the two conditions is related. The current study analyzed the frequency of tooth agenesis and mesiodistal tooth width in cases of hypodontia (1–5 CMT) and oligodontia (≥ 6 CMT) in Japanese patients based on the hypothesis that reductions in mesiodistal tooth width are more frequently associated with oligodontia than hypodontia. Methods Japanese patients with tooth agenesis were divided into hypodontia cases (60 female and 25 male, mean age 19.6 years, mean CMT number 1.31 ± 1.65) and oligodontia cases (26 female and 25 male, mean age 14.6 years, mean CMT number 8.07 ± 2.39). Controls included patients with a skeletal class I relationship and no CMT (female and 60 male, mean age 20.8 years). Dental casts and orthopantomograms were used to analyze the CMT frequency and mesiodistal tooth width for each group. The Kruskal-Wallis test, the Mann-Whitney U test, and Spearman’s rank correlation were used for statistical analysis. Results In the hypodontia group, mandibular second premolars were the most frequently missing tooth type (25.9%), followed by mandibular and maxillary lateral incisors (19.4 and 17.1%, respectively). In the oligodontia group, mandibular second premolars were the most frequently missing tooth type (88.2%), followed by maxillary second premolars (87.3%) and first premolars (63.7%). In female subjects in the hypodontia group, only maxillary lateral incisors and mandibular first molars were significantly smaller than those of the female control subjects. In contrast, in the oligodontia group, more tooth types were significantly smaller than those of the control, for both sexes. Except for maxillary second premolars in female subjects, correlations were apparent for all tooth types in both sexes. Conclusions Compared to hypodontia, more tooth types exhibited reduced mesiodistal tooth width in oligodontia. Correlations between CMT number and mesiodistal tooth width support the hypothesis that reduction of mesiodistal tooth width are more frequently observed in Japanese oligodontia patients than in Japanese hypodontia patients.